Transmutable λ-fold kite systems - Chang, Yanxun; Faro, Giovanni Lo; Tripodi, Antoinette (Utilitas Mathematica, 2008)
Informally, a G-design (X, B) is said to be ∈-transmutable into a G'-design (X, B') if we can take a set D∈ = ∈B : B ∈ B of (isomorphic) edges, one from each copy of G, in such a way there exists a suitable bijection σ between B and D∈ such that B' = (B - ∈B) + σ(B) : B ∈ B. In the case that G is isomorphic to G' we say that the G-design is ∈-switchable. This paper determines the spectrum of λ-fold e-transmutable G-design where G is a kite (a triangle with an edge attached) and G' is either a kite or a 4-cycle.